Territorial Economic Data viewer: A data integration and visualization tool - Anabela Marques Santos; Andrea Conte; Tauno Ojala; Niels Meyer; Ilias Kostarakos; Pietro Santoleri; Yevgeniya Shevtsova; Alicia de Quinto; Francesco Molica; Marie Lalanne (European Commission, Joint Research Centre (JRC), 2023)
The present working paper aims to describe the data sources and methods used to develop the Territorial Economic Data viewer (TEDv), as well as to explain the purpose and usefulness of the different dashboards available in the current version of the tool. Additionally, this paper includes practical examples with policy lessons that can be drawn from the available information, as well as a glossary of the indicators within the TEDv.
Keywords: O31; O20; C81; C82; O18; 330; Data integration; Territorial data visualisation; Policy monitoring